2015
DOI: 10.1016/j.celrep.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

VPS35 Deficiency or Mutation Causes Dopaminergic Neuronal Loss by Impairing Mitochondrial Fusion and Function

Abstract: Vacuolar protein sorting-35 (VPS35) is a retromer component for endosomal trafficking. Mutations of VPS35 have been linked to familial Parkinson’s disease (PD). Here we showed that specific deletion of the VPS35 gene in DA neurons resulted in PD-like deficits including loss of DA neurons and accumulation of α-synuclein. Intriguingly, mitochondria became fragmented and mal-functional in VPS35-deficient DA neurons, phenotypes that could be restored by expressing VPS35 wild type, but not PD-linked mutant. Concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
278
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(289 citation statements)
references
References 43 publications
10
278
1
Order By: Relevance
“…Targeted deletion of VPS35 in mice caused fragmented mitochondria as a result of increased mitochondrial E3 ubiquitin ligase 1 activity and consequent degradation of Mfn2 (Tang et al, 2015). Importantly, stabilization of Mfn2 in the VPS35-deletion model could prevent the loss of dopaminergic neurons (Tang et al, 2015).…”
Section: (2) Additional Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted deletion of VPS35 in mice caused fragmented mitochondria as a result of increased mitochondrial E3 ubiquitin ligase 1 activity and consequent degradation of Mfn2 (Tang et al, 2015). Importantly, stabilization of Mfn2 in the VPS35-deletion model could prevent the loss of dopaminergic neurons (Tang et al, 2015).…”
Section: (2) Additional Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, Mfn2 has been implicated in the function of the retromer component vacuolar protein sorting-35 (VPS35), mutations of which are linked to familial PD (Vilarino-Guell et al, 2011;Zimprich et al, 2011) and also associated with AD (Small et al, 2005;Muhammad et al, 2008). Targeted deletion of VPS35 in mice caused fragmented mitochondria as a result of increased mitochondrial E3 ubiquitin ligase 1 activity and consequent degradation of Mfn2 (Tang et al, 2015). Importantly, stabilization of Mfn2 in the VPS35-deletion model could prevent the loss of dopaminergic neurons (Tang et al, 2015).…”
Section: (2) Additional Neurodegenerative Diseasesmentioning
confidence: 99%
“…Despite these data, it cannot be excluded that CNVs in VPS35 maybe occur in other PD patients groups and contribute to PD onset. It has very recently demonstrated that specific deletion of VPS35 in dopaminergic neurons of deficient mice resulted in PD-like deficits including loss of dopaminergic neurons and accumulation of alpha-synuclein [110].…”
Section: Vps35mentioning
confidence: 99%
“…A recent study has demonstrated that VPS35 depletion in mouse dopamine neurons induces a PD-like condition, including neuronal death, α-synuclein deposition and fragmented mitochondria (Tang et al, 2015). VPS35 depletion or mutation also led to increased levels of the ubiquitin ligase Mul1, which ubiquitylates Mfn2 on the mitochondrial membrane, induces its proteasomal degradation, and may thus promote increased fission-to-fusion and fragmented mitochondria (Tang et al, 2015). Alternatively (or in parallel), a second study provides support for a different model for VPS35 function in the regulation of mitochondrial homeostasis and PD.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial function is closely controlled by their dynamics, and they are continually undergoing cycles of fusion and fission, processes required for homeostasis and mitochondrial health (Chan, 2012). Indeed, perturbations of mitochondrial dynamics have been documented in a wide variety of neurodegenerative disorders, including Alzheimer's disease (Cho et al, 2009) and Parkinson's disease (PD) (Tang et al, 2015). Although the specific mechanisms by which mitochondrial dynamics influence many neurological disorders remain unclear, fusion and fission control mitochondrial size and shape, the number of mitochondria for inheritance in dividing cells, and many mitochondrial functions, such as respiration, cell survival, etc.…”
Section: Introductionmentioning
confidence: 99%